Bioaccumulation of 63Ni in the scleractinian coral Stylophora pistillata and isolated Symbiodinium using radiotracer techniques. (August 2016) - Hédouin, Laetitia; Metian, Marc; Teyssié, Jean-Louis; Oberhänsli, François; Ferrier-Pagès, Christine; Warnau, Michel
Abstract: Development of nickel mining activities along the New Caledonia coasts threatens the biodiversity of coral reefs. Although the validation of tropical marine organisms as bioindicators of metal mining contamination has received much attention in the literature over the last decade, few studies have examined the potential of corals, the fundamental organisms of coral reefs, to monitor nickel (Ni) contamination in tropical marine ecosystems. In an effort to bridge this gap, the present work investigated the bioaccumulation of 63 Ni in the scleractinian coral Stylophora pistillata and in its isolated zooxanthellae Symbiodinium, using radiotracer techniques. Results highlight the high capacities of coral tissues (zooxanthellae and host tissues) to efficiently bioconcentrate 63 Ni compared to skeleton (Concentration Factors CF at 14 days of exposure are 3 orders of magnitude higher in tissues than in skeleton). When non-contaminated conditions were restored, 63 Ni was more efficiently retained in skeleton than in coral tissues, with biological half-lives (Tb½ ) of 44.3 and 6.5 days, respectively. In addition, our work showed that Symbiodinium bioconcentrated 63 Ni exponentially, with a vol/vol concentration factor at steady state (VCFSS ) reaching 14, 056. However, compilation of our results highlighted that despite efficient bioconcentration of 63 Ni in Symbiodinium, their contribution to the whole 63 Ni accumulation in coral nubbins represents less than 7%, suggesting that other biologically controlled processes occur in coral host allowing such efficient bioconcentration in coral tissues. Highlights: High bioaccumulation of Ni in coral tissues of Stylophora pistillata . Concentrations of Ni 63 in tissues are 3 orders of magnitude higher than those in skeleton. Low contribution of zooxanthellae into the global bioaccumulation of Ni in coral.